Open fracture-dislocation of the knee associated with nonunion of the medial femoral condyle and chronic tendon patellar rupture - Calderazzi, Filippo; Visigalli, Alberto; Scita, Giacomo; Spirito, Alessandro; Ferrari, Umberto; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of work:The incidence of coronal fractures of the femoral condyle, Hoffa fractures, ranges from 8.7% to 13% of all fractures of the distal femur and are often observed in polytraumas.Hoffa fractures may be misdiagnosed and consequently not properly treated. Reduction and synthesis of this type of fracture should be achieved to avoid complications such as nonunion, pain, functional impairment.The authors present a case of a 5 year old nonunion of a Hoffa fracture of the medial condyle with chronic patellar tendon rupture. Methods:Revision surgery consisted of reduction and fixation of the Hoffa fracture with screws associated with bone grafting from the iliac crest. Distalization of the patella by Z-plasty and reconstruction of the patellar tendon with Achille's allograft were also performed. Results:Clinical evaluation after 10 months following the end of the treatment showed a complete resolution of pain, almost complete range of motion, good strength and almost complete functionality of the operated limb. ConclusionsMistakes in the diagnosis or treatment of Hoffa fracture can often result nonunion, functional impairment, and persistent pain.To avoid these, the senior authors of this text believe that the correct treatment of acute Hoffa fracture and its potential associated injuries are crucial, according to the concept of early damage control and later synthesis with soft tissue reconstruction.